2017
DOI: 10.1177/1176934317700863
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Enterobacterium Pragia fontium 24613: Complete Genome Sequence and Metabolic Profiling

Abstract: Pragia fontium is one of the few species that belongs to the group of atypical hydrogen sulfide-producing enterobacteria. Unlike other members of this closely related group, P. fontium is not associated with any known host and has been reported as a free-living bacterium. Whole genome sequencing and metabolic fingerprinting confirmed the phylogenetic position of P. fontium inside the group of atypical H2S producers. Genomic data have revealed that P. fontium 24613 has limited pathogenic potential, although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…and Leminorella spp., and it contains only one species, P. fontium, a free-living bacterium isolated from an environment that under anaerobic conditions utilizes monosaccharides and their derivatives but lacks fatty acid degradation pathways (Snopková et al 2017). The genus Budvicia has been identified in the red palm weevil (Tagliavia et al 2014), while Pragia was previously found to be associated with the gut of Poecilus chalcites (Lehman et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Leminorella spp., and it contains only one species, P. fontium, a free-living bacterium isolated from an environment that under anaerobic conditions utilizes monosaccharides and their derivatives but lacks fatty acid degradation pathways (Snopková et al 2017). The genus Budvicia has been identified in the red palm weevil (Tagliavia et al 2014), while Pragia was previously found to be associated with the gut of Poecilus chalcites (Lehman et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…fontium, a free‐living bacterium isolated from an environment that under anaerobic conditions utilizes monosaccharides and their derivatives but lacks fatty acid degradation pathways (Snopková et al. 2017). The genus Budvicia has been identified in the red palm weevil (Tagliavia et al.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S mainly results from the fermentation of undigested sulphur protein in the hindgut, as well as the reduction of oxidized inorganic sulphur compounds, such as sulphate radicals (SO 4 2− ), by sulphur-reducing bacteria (SRB) [ 17 , 19 ]. There are many bacterial genera involved in sulphate reduction or protein degradation, such as Desulfovibrio , Veillonella , Megasphaera and Enterobacteria [ 20 , 21 , 22 ]. A previous study indicated that, under similar environments, host species have the potential to affect the composition of intestinal microorganisms, including some gas-producing ones [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%